2024
DOI: 10.1073/pnas.2313661121
|View full text |Cite
|
Sign up to set email alerts
|

Excess natural-cause mortality in US counties and its association with reported COVID-19 deaths

Eugenio Paglino,
Dielle J. Lundberg,
Elizabeth Wrigley-Field
et al.

Abstract: In the United States, estimates of excess deaths attributable to the COVID-19 pandemic have consistently surpassed reported COVID-19 death counts. Excess deaths reported to non-COVID-19 natural causes may represent unrecognized COVID-19 deaths, deaths caused by pandemic health care interruptions, and/or deaths from the pandemic’s socioeconomic impacts. The geographic and temporal distribution of these deaths may help to evaluate which explanation is most plausible. We developed a Bayesian hierarchical model to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The proportion of deaths at home also increased during the pandemic 35 , reducing the opportunity for a COVID-19 diagnosis. The political polarization of COVID-19 in the US may have contributed to underreporting that varied by geography 36 . In addition to misattributed COVID-19 mortality, increases in CVD mortality may have occurred due to disruptions in routine or emergency health services during COVID-19 peaks 37 or healthcare avoidance due to fear of infection.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of deaths at home also increased during the pandemic 35 , reducing the opportunity for a COVID-19 diagnosis. The political polarization of COVID-19 in the US may have contributed to underreporting that varied by geography 36 . In addition to misattributed COVID-19 mortality, increases in CVD mortality may have occurred due to disruptions in routine or emergency health services during COVID-19 peaks 37 or healthcare avoidance due to fear of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies aim to assess the number of unrecognised COVID-19 deaths [ 23 ], but the COVID-19 mentions reported as a comorbidity have never been examined for this purpose. Our study found that 8% of death certificates citing COVID-19 reported it only as a comorbidity, more frequently in Austria, Bavaria, Czechia and Lithuania than in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…While the importance of these factors can be approximated by studying mortality from causes other than COVID-19, the scale of unrecognised coronavirus cases has rarely been explored due to lack of data and methods. The most recent study [ 23 ] showing that peaks in COVID-19 deaths were preceded at short time intervals by peaks of all-cause mortality in some regions of the United States is a novelty in this respect. This study shows that despite the complexity of the pathophysiological process leading to death in the presence of SARS-CoV-2, the use of MCoD data and metrics allows us to overcome some of the ambiguity of certification practices and to assess the overall burden of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation